Online newspapers reporting of homeland politics to diasporic nigerians during the 2011 Nigerian presidential election: a perspective from Malaysia - Mustapha, Lambe Kayode; Wok, Saodah (The World Bank, 2014)
This study presented what Nigerian newspapers on the Web beamed to Nigerian foreign resident citizens during the 2011 Nigerian presidential election. Premised on the importance of diaspora to homeland political development and the centrality of the web media to the migrants in today's globalized world, the paper explored how homeland online newspapers connected the diaspora with Nigerian political transition. By content analyzing three major Nigerian online newspapers, the Daily Trust, the Punch, and the Vanguard, the paper concentrated on the supply side of information to Nigerians in diaspora, thus inundating them with what to think and how to think about the election and the candidates. Beyond presenting the key issues and candidates' attributes covered in the online newspapers (the predictor variable in agenda-setting study) during the presidential election, this study found that Nigerian online newspapers prioritized election issues and candidates' attributes differently for the main contenders in the election. The paper thus challenged the Nigerian media to consider their diasporic audience in their news production and distribution, particularly in the light of increasing agitations for direct political participation among Nigerians in diaspora.